Method of correcting stitching errors in reconstructing a synthetic-aperture digital hologram with seams. Issue 7 (16th April 2019) - Ding, Meng; Fan, Qi; Su, Yin; Yang, Baiyu; Tian, Changhui; Wang, Binke; Wang, Yunfei
ABSTRACT: We propose a correction method based on the shift theorem of the Fourier transform for the non-integer pixel stitching error in a synthetic-aperture digital hologram with seams. After being Fourier transformed, the sub-holograms stemming from the dislocated recording planes are multiplied by a phase factor and then superposed onto in-place sub-holograms. Finally, the entire hologram is inverse Fourier transformed for reconstruction. This method is applied to simulated particle detection. The results show that the correlation coefficient (CC) between the reconstructed image and the simulated target image is 1.5 times, by comparison with an image that does not involve the phase-factor correction, and particles at the seams are clearly visible. In addition, the effect of noise on the method is small. These verify the feasibility of the method.